2017
DOI: 10.1681/asn.2016101053
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ferric Citrate in Patients with Nondialysis-Dependent CKD and Iron Deficiency Anemia

Abstract: Iron deficiency anemia is common and consequential in nondialysis-dependent CKD (NDD-CKD). Efficacy and tolerability of conventional oral iron supplements are mixed; intravenous iron administration associates with finite but important risks. We conducted a randomized double-blind clinical trial in adults with NDD-CKD and iron deficiency anemia to compare the safety and efficacy of oral ferric citrate (n=117) and placebo (n=115). The primary end point was the proportion of patients who achieved a $1.0 g/dl incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
133
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 95 publications
(135 citation statements)
references
References 31 publications
2
133
0
Order By: Relevance
“…Uptake of citrate through short chain fatty acid transporters by colonic epithelial cells can be, in turn, followed by uptake of iron to maintain electrical neutrality. This phenomenon may account for atypical iron absorption in the reported FC-treated CKD patients (Block et al, 2015;Lewis et al, 2015;Tanaka et al, 2016;Fishbane et al, 2017) and CKD rats shown in our study by bypassing the normal route of iron absorption.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Uptake of citrate through short chain fatty acid transporters by colonic epithelial cells can be, in turn, followed by uptake of iron to maintain electrical neutrality. This phenomenon may account for atypical iron absorption in the reported FC-treated CKD patients (Block et al, 2015;Lewis et al, 2015;Tanaka et al, 2016;Fishbane et al, 2017) and CKD rats shown in our study by bypassing the normal route of iron absorption.…”
Section: Discussionmentioning
confidence: 55%
“…Due to impaired iron absorption, most ESRD patients are routinely treated with intravenous iron products. However, oral administration of FC has been reported to expand iron stores and lower the need for parenteral iron products in the CKD and ESRD populations (Block et al, 2015;Lewis et al, 2015;Tanaka et al, 2016;Fishbane et al, 2017). To our knowledge the This article has not been copyedited and formatted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a randomized placebo‐controlled trial of ferric citrate in 234 patients with NDD‐CKD and iron deficiency anemia,2 ferric citrate‐treated patients were significantly more likely to achieve a ≥1.0 g/dL increase in hemoglobin (52.1% vs. 19.1% with placebo; P  < .001) during the 16‐week randomized phase; the least‐squares mean (LSM) relative change in hemoglobin was 0.84 g/dL (95% confidence interval [CI], 0.58‐1.10) 2…”
mentioning
confidence: 99%
“…Full clinical trial details are described elsewhere 2. Here, multivariable linear regression analysis was used to identify variables associated with change in hemoglobin from baseline to week 16.…”
mentioning
confidence: 99%